2003
DOI: 10.1093/aje/kwf209
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Cognitive Function and Mortality in Middle-aged Adults: The Atherosclerosis Risk in Communities Study

Abstract: An independent, inverse association between cognitive function and all-cause mortality has been reported in elderly cohorts. The purpose of this study was to determine whether the same association exists in middle-aged persons. The Atherosclerosis Risk in Communities Study is a cohort study initiated in 1987 to investigate the development of atherosclerosis in middle-aged persons. Three cognitive function measures were included in the second cohort examination conducted from 1990 to 1992 when the participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 21 publications
6
69
1
Order By: Relevance
“…The association between cognition and mortality appears robust and most measures of cognition have been shown to be associated with mortality (Anstey et al, 2001;Hassing et al, 2002;Korten et al, 1999;Pavlik et al, 2003;Portin et al, 2001;Shipley et al, 2006;Small et al, 2003;Smits et al, 1999). However, comparisons between different cognitive measures in the elderly reveal, in one study, visuospatial reasoning, verbal fluency and short-term but not working memory to be associated with mortality (Small et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The association between cognition and mortality appears robust and most measures of cognition have been shown to be associated with mortality (Anstey et al, 2001;Hassing et al, 2002;Korten et al, 1999;Pavlik et al, 2003;Portin et al, 2001;Shipley et al, 2006;Small et al, 2003;Smits et al, 1999). However, comparisons between different cognitive measures in the elderly reveal, in one study, visuospatial reasoning, verbal fluency and short-term but not working memory to be associated with mortality (Small et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…The explanatory variables previously examined to explore the association between cognition and mortality have included socioeconomic variables (Anstey et al, 2001;Hart et al, 2005;Hassing et al, 2002;Korten et al, 1999;Kuh et al, 2004;Pavlik et al, 2003;Portin et al, 2001;Shipley et al, 2006;Small et al, 2003;Small and Backman, 1997;Smits et al, 1999;Whalley and Deary, 2001), health behaviours (Holsinger et al, 2007;Korten et al, 1999;Kuh et al, 2004;Pavlik et al, 2003;Shipley et al, 2006) and measures of health (Anstey et al, 2001;Hassing et al, 2002;Holsinger et al, 2007;Korten et al, 1999;Kuh et al, 2004;Pavlik et al, 2003;Portin et al, 2001;Shipley et al, 2006;Small et al, 2003;Smits et al, 1999). The different results on the role played by explanatory variables are probably due to differences in measures of cognition and the covariates examined.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research has consistently demonstrated that poor cognitive function is associated with increased mortality risk in older populations (Gale et al 1996;Pavlik et al 2003;Perna et al 2015). In contrast, studies on predictive abilities of cognitive decline beyond current levels of cognitive function have reached competing conclusions (Maier et al 2003;Schupf et al 2005;Ghisletta 2008;Lavery et al 2009).…”
Section: Sex Differences In Cognitive Functionmentioning
confidence: 99%
“…During the last decade, investigators began to examine the predictive significance of IQ for health outcomes (1). Several studies of middle-aged (2,3) and, particularly, older-aged (4,5) adults found that those with higher scores on tests of mental ability had lower rates of later all-cause mortality. These associations may occur across the full range of test scores (6,7), rather than just in persons with severe mental impairment, although this is not a universal observation (4).…”
Section: Introductionmentioning
confidence: 99%